2021
DOI: 10.1002/oby.23206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of severe obesity and sleeve gastrectomy on cortical thickness in adolescents

Abstract: Objective: Neurocognitive differences in pediatric obesity may be underpinned by cortical structural alterations. Differences in cortical thickness associated with severe obesity were examined, and preliminary evidence was sought for changes following vertical sleeve gastrectomy (VSG).Methods: A total of 18 adolescents with severe obesity (OB) and 17 without obesity (nOB), aged 14 to 21, underwent T1-weighted structural magnetic resonance imaging.A subset was scanned twice 5 months apart to compare cortical th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…While the culturing of primary rodent and iPSC-derived neurons in two-dimensional monolayers is a common approach to study neuronal biology in vitro, the use of three-dimensional (3D) neurosphere models to more accurately reflect the microenvironment of the brain has gained traction as a discovery model [ 32 ]. We have recently developed a protocol for generating high-quality, reproducible 3D cortical neurosphere cultures [ 33 ]. Two PD patient-derived iPSC lines harboring either the A53T mutation or gene triplication (S3) in the SNCA gene were used to evaluate the effect of SCD inhibition by YTX-7739 on multiple disease-relevant phenotypes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the culturing of primary rodent and iPSC-derived neurons in two-dimensional monolayers is a common approach to study neuronal biology in vitro, the use of three-dimensional (3D) neurosphere models to more accurately reflect the microenvironment of the brain has gained traction as a discovery model [ 32 ]. We have recently developed a protocol for generating high-quality, reproducible 3D cortical neurosphere cultures [ 33 ]. Two PD patient-derived iPSC lines harboring either the A53T mutation or gene triplication (S3) in the SNCA gene were used to evaluate the effect of SCD inhibition by YTX-7739 on multiple disease-relevant phenotypes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to aberrant fatty acid desaturation, A53T and S3 neurospheres accumulated total αSyn and pS129 αSyn levels as compared to their respective isogenic control neurospheres [ 33 ]. The abnormal accumulation of total and pS129 αSyn is a pathological hallmark observed in PD patient cells and several in vitro and in vivo model systems of PD [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding brain morphology, associations between childhood obesity and cortical thickness have been found in diverse brain regions. Many studies have reported association to areas within the frontal lobe [9][10][11][12][13][14] . Yet, other brain regions may also play a role 15 .…”
Section: Main Textmentioning
confidence: 99%
“…Cortical surface area predicted subsequent BMI changes during adolescence (41). An experimental study observing brain morphology changes following bariatric surgery found an effect of childhood obesity on cortical thickness (12). Genetically informed analyses revealed directional effects from polygenic scores for BMI to ADHD, heavy smoking (42), and overeating (43), as well as cortical volume (44).…”
Section: Introductionmentioning
confidence: 99%